Electrical conduction mechanism in Se90-xTe5Sn5Inx (x = 0, 3, 6 and 9) multi-component glassy alloys - Ram I.S.; Kumar S.; Singh R.K.; Singh P.; Singh K. (My University, 2025)
Electrical conductivity of Se90-xTe5Sn5Inx (x = 0, 3, 6 and 9) glassy systems was studied employing impedance spectroscopic technique in the frequency range 100 Hz to 1 MHz and in the temperature range 308-388 K. The DC conductivity (σdc) at each temperature was evaluated from the low frequency plateau region for all the samples under investigation. The bulk conductivity for each sample was also evaluated from Nyquist impedance plots. The semicircle shape of Nyquist plot exhibit dipolar nature of samples. The activation energy for glassy, amorphous and crystalline region from the Arrhenius plot of the DC conductivity and bulk conductivity was evaluated. From the results it is found that activation energy varied from 0.091 to 0.194 eV in glassy, 0.686 to 0.002 eV in amorphous and 0.215 to 0.503 eV in crystalline region. The activation energy (ΔE) from DC conductivity and bulk conductivity found to be close in corresponding regions. The pre-exponential factor was also calculated for all three regions. © 2015 Author(s).